Preparation and Characterization of Dextrin in Xanthosoma sagittifolium (L.) Schott Starch with Acid Catalyst and Enzymatic Methods - Karsono; Sumaiyah; Wiliantari, Selvia (Indonesian Journal of Pharmaceutical and Clinical Research, 2018)
Abstract. Taro produces carbohydrate. It has the potential as a substitute material for wheat and rice or as diversification into food and raw materials for pharmaceutical industrial. The aim of this study is to prepare and characterize dextrin in Xanthosoma sagittifolium starch with acid catalyst and enzymatic methods. Xanthosoma sagittifolium was mashed and decanted with distilled water. Dextrin was made by acid catalyst method using HCl 1 N and enzymatic method using α-amylase enzyme. Dextrin was characterized and tested according to the Indonesian National Standard (SNI) 01-2593-1992. The results showed that the yield from acid catalyst and enzymatic methods are 41.73 % and 67.10 %, respectively. The color test showed that dextrin from acid catalyst method is yellowish whereas the enzymatic method gives white dextrin. The qualitative test with lugol solution gives brownish purple dextrin. The characteristic of 80 mesh fineness for dextrin fabricated by acid and enzymatic methods are 94.7 % ± 0.06 and 93.96 % ± 0.02 respectively. Dextrin obtained from acid catalyst has higher water content (8.79 % ± 0.15) than dextrin from enzymatic methods (7.62 % ± 0.23) as well as dextrin from acid catalyst has higher the ash content (0.45 % ± 0.02) than dextrin from enzymatic method (0.42 % ± 0.04). Dextrin made from enzymatic method has higher solubility in cold water (63.09 % + 0.1) than dextrin from acid catalyst method (57.47 % ± 0.25). Dextrose equivalent for dextrin produced is 13.65 ± 0.36 and 15.31 ± 0.46 for acid catalyst and enzymatic methods. Melting points for dextrin obtained from acid catalyst and enzymatic methods are 185 oC ± 0.57 and 182 cC ± 0.57 respectively. Acidity degree of dextrin fabricated from acid catalyst and enzymatic methods are 2.86 ± 0.23 and 4.39 ± 0.4. The research shows that the characterization of dextrin by acid catalyst and enzymatic methods meet the quality requirements for Indonesia National Standard (SNI) 01-2593-1992. Key words: Taro, dextrin, acid catalyst method, enzymatic method